Pengembangan Modul Pembelajaran Fisika Kelas XI MA/SMA Berbasis Guided Inquiry pada Materi Alat-Alat Optik - Lutfita Mukharovatun Azizah; Joko Budi Poernomo; Muhammad Izzatul Faqih (Physics Education Research Journal, 2019)
This study aims to produce guided inquiry based learning modules on optical instrument material and test their effectiveness. This research and development refers to the modified Borg and Gall (1983) model. Techniques for collecting data through observation, questionnaires, tests and documentation. The results of the feasibility test showed that the physics learning module based on guided inquiry on optical instrument material was feasible to use with the percentage of the feasibility score from the material experts amounting to 87.27% and from media experts amounting to 91.67%. The effectiveness test results show that the module produced effectively. This is indicated by the results of t-test calculations on student learning outcomes test data obtained ttable 2.048 and tcount of 6.433, so tcountttable which means ????0 is rejected, ???????? is accepted.